Pengembangan Lembar Kerja Peserta Didik Berbantuan Kartu Domino Fisika Pada Materi Cahaya Dan Alat Optik - Wilibrodus Koi; Maria Ursula Jawa Mukin; Oktavianus Ama Ki`i; Alfons Bunga Naen; Isabel Coryunitha Panis; Rosenti Pasaribu (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2024)
The problem faced in learning Physics is the lack of a variety of interesting and interactive learning media, which can affect students' interest and understanding of the material being taught. In an effort to overcome this problem, a Physics Domino Card-assisted LKPD was developed as an innovative learning media. This study aims to determine the feasibility of Learner Worksheets (LKPD) assisted by Physics Domino Cards on the material of Light and Optical Instruments; to determine the response of students to the implementation of learning activities using the LKPD. This research is a development research using the 4-D model (Four D Model), which consists of the defining stage (define), the planning stage (design), the development stage (development), and the disseminate stage (disseminate). The instruments used include product validation sheets and student response questionnaire sheets. The data analysis technique used is descriptive analysis, namely product validation analysis using the V Aiken coefficient and analysis of learner responses using percentages. The results of the validation analysis showed that the LKPD assisted by Domino Card Physics obtained a V Aiken coefficient of 0,86 which was categorized as very valid. Students' responses to the use of LKPDs assisted by Physics Domino Cards as learning media showed a percentage of 89%, which was categorized as very good. LKPD assisted by Physics Domino Cards on the material of Light and Optical Instruments is very feasible to use and get a very good response from students, so it can be used as an alternative learning media that is effective in increasing students' interest and understanding of Physics material.